-
Notifications
You must be signed in to change notification settings - Fork 1
/
Copy pathParallel.agda
160 lines (125 loc) · 4.7 KB
/
Parallel.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
import Relation.Binary.PropositionalEquality as Eq
open Eq using (_≡_; refl; subst₂; cong)
open import Data.Nat.Base
open import Data.Fin hiding (_+_; #_)
open import Data.Product using (∃; _×_; _,_; ∃-syntax)
open import DeBruijn
open import Substitution using (rename-subst-commute; subst-commute)
open import Beta
infix 3 _⇉_
data _⇉_ : ∀ {n} → Term n → Term n → Set where
⇉-c : ∀ {n} {x : Fin n}
---------
→ # x ⇉ # x
⇉-ƛ : ∀ {n} {M M′ : Term (suc n)}
→ M ⇉ M′
----------
→ ƛ M ⇉ ƛ M′
⇉-ξ : ∀ {n} {M M′ N N′ : Term n}
→ M ⇉ M′
→ N ⇉ N′
---------------
→ M · N ⇉ M′ · N′
⇉-β : ∀ {n} {M M′ : Term (suc n)} {N N′ : Term n}
→ M ⇉ M′
→ N ⇉ N′
---------------------
→ (ƛ M) · N ⇉ M′ [ N′ ]
par-subst : ∀ {n m} → Subst n m → Subst n m → Set
par-subst σ σ′ = ∀ {x} → σ x ⇉ σ′ x
par-rename : ∀ {n m} {ρ : Rename n m} {M M′ : Term n}
→ M ⇉ M′
------------------------
→ rename ρ M ⇉ rename ρ M′
par-rename ⇉-c = ⇉-c
par-rename (⇉-ƛ p) = ⇉-ƛ (par-rename p)
par-rename (⇉-ξ p₁ p₂) = ⇉-ξ (par-rename p₁) (par-rename p₂)
par-rename {n}{m}{ρ} (⇉-β {n}{N}{N′}{M}{M′} p₁ p₂)
with ⇉-β (par-rename {ρ = ext ρ} p₁) (par-rename {ρ = ρ} p₂)
... | G rewrite rename-subst-commute {n}{m}{N′}{M′}{ρ} = G
par-subst-exts : ∀ {n m} {σ σ′ : Subst n m}
→ par-subst σ σ′
---------------------------
→ par-subst (exts σ) (exts σ′)
par-subst-exts s {x = zero} = ⇉-c
par-subst-exts s {x = suc x} = par-rename s
subst-par : ∀ {n m} {σ σ′ : Subst n m} {M M′ : Term n}
→ par-subst σ σ′
→ M ⇉ M′
----------------------
→ subst σ M ⇉ subst σ′ M′
subst-par {M = # x} s ⇉-c = s
subst-par {n}{m}{σ}{σ′} {ƛ N} s (⇉-ƛ p) =
⇉-ƛ (subst-par {σ = exts σ}{σ′ = exts σ′}
(λ {x} → par-subst-exts s {x = x}) p)
subst-par {M = L · M} s (⇉-ξ p₁ p₂) =
⇉-ξ (subst-par s p₁) (subst-par s p₂)
subst-par {n}{m}{σ}{σ′} {(ƛ N) · M} s (⇉-β {M′ = M′}{N′ = N′} p₁ p₂)
with ⇉-β (subst-par {σ = exts σ}{σ′ = exts σ′}{M = N}
(λ {x} → par-subst-exts s {x = x}) p₁)
(subst-par {σ = σ} s p₂)
... | G rewrite subst-commute {N = M′}{M = N′}{σ = σ′} = G
par-subst-zero : ∀ {n} {M M′ : Term n}
→ M ⇉ M′
----------------------------------------
→ par-subst (subst-zero M) (subst-zero M′)
par-subst-zero M⇉M′ {zero} = M⇉M′
par-subst-zero M⇉M′ {suc x} = ⇉-c
sub-par : ∀ {n} {M M′ : Term (suc n)} {N N′ : Term n}
→ M ⇉ M′
→ N ⇉ N′
-------------------
→ M [ N ] ⇉ M′ [ N′ ]
sub-par M⇉M′ N⇉N′ = subst-par (par-subst-zero N⇉N′) M⇉M′
par-refl : ∀ {n} {M : Term n}
-----
→ M ⇉ M
par-refl {M = # x} = ⇉-c
par-refl {M = ƛ N} = ⇉-ƛ par-refl
par-refl {M = L · M} = ⇉-ξ par-refl par-refl
beta-par : ∀ {n} {M N : Term n}
→ M —→ N
------
→ M ⇉ N
beta-par {M = L · M} (—→-ξₗ r) = ⇉-ξ (beta-par {M = L} r) par-refl
beta-par {M = L · M} (—→-ξᵣ r) = ⇉-ξ par-refl (beta-par {M = M} r)
beta-par {M = ƛ N} (—→-ƛ r) = ⇉-ƛ (beta-par r)
beta-par {M = (ƛ N) · M} —→-β = ⇉-β par-refl par-refl
par-betas : ∀ {n} {M N : Term n}
→ M ⇉ N
------
→ M —↠ N
par-betas {M = # _} (⇉-c {x = x}) = # x ∎
par-betas {M = ƛ M} (⇉-ƛ p) = —↠-cong-ƛ (par-betas p)
par-betas {M = M · N} (⇉-ξ p₁ p₂) = —↠-cong (par-betas p₁) (par-betas p₂)
par-betas {M = (ƛ M) · N} (⇉-β {M′ = M′}{N′ = N′} p₁ p₂) =
let a : (ƛ M) · N —↠ (ƛ M′) · N
a = —↠-congₗ (—↠-cong-ƛ (par-betas p₁))
b : (ƛ M′) · N —↠ (ƛ M′) · N′
b = —↠-congᵣ (par-betas p₂)
c = (ƛ M′) · N′ —→⟨ —→-β ⟩ M′ [ N′ ] ∎ in
—↠-trans (—↠-trans a b) c
infix 3 _⇉*_
infixr 3 _⇉⟨_⟩_
infix 4 _∎
data _⇉*_ : ∀ {n} → Term n → Term n → Set where
_∎ : ∀ {n} (M : Term n)
------
→ M ⇉* M
_⇉⟨_⟩_ : ∀ {n} {L N : Term n} (M : Term n)
→ M ⇉ L
→ L ⇉* N
------
→ M ⇉* N
betas-pars : ∀ {n} {M N : Term n}
→ M —↠ N
------
→ M ⇉* N
betas-pars (M ∎) = M ∎
betas-pars (M —→⟨ b ⟩ bs) = M ⇉⟨ beta-par b ⟩ betas-pars bs
pars-betas : ∀ {n} {M N : Term n}
→ M ⇉* N
------
→ M —↠ N
pars-betas (M ∎) = M ∎
pars-betas (M ⇉⟨ p ⟩ ps) = —↠-trans (par-betas p) (pars-betas ps)